Sistema de informações gerenciais e os métodos de apoio à tomada de decisão: um estudo com gestores das empresas de capital aberto - Copi Junior, Ulisses (2009)
The extremely competitive scenario in which the organizations are involved demands from managers a high level of rationality due to the difficulties that arise at key decision making moment, when they face the necessity to evaluate the alternatives available to them, utilizing quantitative and qualitative criteria. In this context, managers have tools available, like the Management Information System and the Decision Support System, that help make the decision making process transparent and to justify the decision. To support the sustainability and continuity of the company, the decisions must be aligned with its values, beliefs and principles, in other words, with the Managerial Model adopted. This Model must serve as a support to the Management Information Systems concept. Although the Management Information System is widely distributed and utilized by managers, the Support Decision Systems are not. The objective of this study is to identify if the public company s managers are aware of and make use of MIS and the Support Decision Systems as tools to support the decision making process. Additionally the study aims to verify if, in the opinion of the selected companies managers, the Managerial Model is reflected in the adopted MIS. This study was performed as a survey, in which 504 public company s managers participated. The survey, performed with closed questions, questions with responses required to be put in order of importance, and questions requiring scoring, were statistically treated, using the statistical software SPSS version 16.0. The results were analyzed and it was verified that, although the researched companies managers either make use of MIS as a tool to support the decision making process or consider important the Support Decision Systems, they are not aware of the more sophisticated multi-feature methods